Biomaterials: A potential pathway to healing chronic wounds?. Issue 9 (14th February 2017) - Pop, Mara A.; Almquist, Benjamin D.
Abstract: Chronic dermal wounds are a devastating problem, which disproportionally affect individuals with conditions such as diabetes, paralysis, or simply old age. These wounds are extremely challenging to treat due to a heterogeneous combination of causative factors, creating a substantial burden on healthcare systems worldwide. Despite their large impact, there is currently a startling lack of options for effectively treating the underlying biological changes that occur within the wounds. Biomaterials possess an enticing ability to provide new comprehensive approaches to healing these devastating wounds; advanced wound dressings are now being developed that enable the ability to coordinate temporal delivery of multiple therapeutics, protect sensitive biologics from degradation, and provide supportive matrices that encourage the growth of tissue. This positions biomaterials as a potential "conductor" of wound repair, allowing them to simultaneously address numerous barriers to healing, and in turn providing a promising pathway to innovative new technologies for driving successful healing.